PERANCANGAN KOMUNIKASI VISUAL PERMAINAN PAPAN CINTA KULINER SUMATERA SELATAN - Jessica Halim; Yosef Yulius; Heri Iswandi (Besaung : Jurnal Seni Desain dan Budaya, 2017)
Indonesia has a range of distinctive cultures, one of which in the field of culinary. Culture can be preserved if it continues to be inherited from generation to generation, however the development of lifestyle and technology can lead to culture is threatened to be maintained. So, a design in culinary-themed board game from South Sumatra is made for that situation. This board game is aiming to introduce the typical food from South Sumatra in interesting ways as well as fun. In addition, this board game can help parents and teachers educate the children, also giving the value of cognitive, social, and positive emotions for children. Key words: Children, Board Game, Culinary, South Sumatera.